PENILAIAN TERHADAP LAPORAN KEUANGAN DENGAN PERSENTASE PER KOMPONEN PADA PERUSAHAAN SEKTOR PERBANKAN PT BNI TBK - Maharani, Amandasiwi Nabillah; Sulistyo, Hari (Jurnal Akuntansi AKTIVA, 2025)
This research aims to evaluate the improvement in financial performance of PT. Bank Negara Indonesia (BNI) Tbk from 2020 to 2021 using percentage analysis per component or common size. The percentage analysis for each component will serve as a basis for consideration and decisions. In this research, the organization's annual financial reports will be analyzed to assess financial performance. This will be done using a percentage analysis technique per component. Therefore, the company's financial statements will help draw favorable conclusions about the company's financial performance. This research will discuss the balance sheet and profit and loss reports of PT. BNI during the 2020-2021 period because this research uses percentage analysis per component. There are two methods used to collect data: documentation and quantitative research methods. Studies show that the assets of PT. BNI is not comparable to non-current assets because most of it is used as company capital. As a result, the company's level of solvability decreases and creditors may have a low margin of safety because the company uses capital for most of its assets and liabilities. However, PT. BNI showed a significant increase from 2020 to 2021, indicating the company's financial performance was better and relatively stable.